Tipologi dan Klasifikasi Perangkat Daerah: Analisis Struktur dan Fungsinya dalam Tata Pemerintahan Daerah - Sri Yulianty Mozin; Siti Nurcahyati Abdussamad; Sabrina Meamogu (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This article examines the typology and classification of regional government apparatus in Indonesia by analyzing their structure and functions within local governance. The study draws on recent theoretical literature (2020–2025) and legal frameworks to map how different types of regional apparatus such as executive agencies (“dinas”), supporting agencies (“badan daerah”), secretariat, inspectorate, and territorial units are organized and classified. Using a normative-juridical and conceptual approach, the paper reviews relevant laws, regulations, and academic studies to identify patterns of structural typology and functional differentiation within local governments. The findings reveal that many local governments still apply structural-heavy models rather than functionally tailored organizations, leading to excessive bureaucracy and inefficiency. The analysis suggests that a clearer classification aligned with functional roles can improve governance effectiveness and administrative efficiency. The article concludes by recommending that local governments re-evaluate their organizational structures to better reflect the functional needs of governance, rather than merely replicate structural models.